Anti-inflammatory activity of Jefea gnaphalioides (a. gray), Astereaceae - Axel Villagómez-Rodríguez; Julia Pérez-Ramos; Ana Laura Esquivel-Campos; Cuauhtémoc Pérez-González; Claudia Angélica Soto-Peredo; Salud Pérez-Gutiérrez (BMC, 2019)
Abstract Background Inflammation is a symptom associated with many diseases. This symptom is treated with steroidal and non-steroidal anti-inflammatory drugs, which can cause severe side effects when used as long-term treatments. Natural products are an alternative source of new compounds with anti-inflammatory activity. Jefea gnaphalioides (Astereaceae) (A. Gray) is a plant species used to treat inflammatory problems, in Mexico. This study determined the anti-inflammatory activity and the composition of the methanol extract of Jefea gnaphalioides (MEJG). Methods The extract was obtained by heating the plant in methanol at boiling point for 4 h, and then the solvent was evaporated under vacuum (MEJG). The derivatization of the extract was performed using Bis-(trimethylsilyl) trifluoroacetamide, and the composition was determined by GC-MS. Total Phenols and flavonoids were determined by Folin-Ciocalteu AlCl3 reaction respectively. The antioxidant activity of MEJG was determined by DPPH method. The acute and chronic anti-inflammatory effects were evaluated on a mouse ear edema induced with 12-O-Tetradecanoylphorbol-13-acetate (TPA). Acute oral toxicity was tested in mice at doses of MEJG of 5000, 2500 and 1250 mg/kg. The levels of NO, TNF-α, IL-1β and IL-6 were determinate in J774A.1 macrophages stimulated by Lipopolysaccharide. The production of inflammatory interleukins was measured using commercial kits, and nitric oxide was measured by the Griess reaction. Results The anti-inflammatory activity of MEJG in acute TPA-induced ear edema was 80.7 ± 2.8%. This result was similar to the value obtained with indomethacin (IND) at the same dose (74.3 ± 2.8%). In chronic TPA-induced edema at doses of 200 mg/kg, the inhibition was 45.7%, which was similar to that obtained with IND (47.4%). MEJG have not toxic effects even at a dose of 5000 mg/kg. MEJG at 25, 50, 100 and 200 μg/mL decreased NO, TNF-α, IL-1β and IL-6 production in macrophages stimulated with LPS. The major compounds in MEJG were α-D-Glucopyranose (6.71%), Palmitic acid (5.59%), D-(+)-Trehalose (11.91%), Quininic acid (4.29%) and Aucubin (1.17%). Total phenolic content was 57.01 mg GAE/g and total flavonoid content was 35.26 mg QE/g MEJG had antioxidant activity. Conclusions MEJG has anti-inflammatory activity.